Do Unto Others: Doctors' Personal End-of-Life Resuscitation Preferences and Their Attitudes toward Advance Directives - Periyakoil, Vyjeyanthi S. (Public Library of Science, 2014)
OBJECTIVE: High-intensity interventions are provided to seriously-ill patients in the last months of life by medical sub-specialists. This study was undertaken to determine if doctors' age, ethnicity, medical sub-specialty and personal resuscitation and organ donation preferences influenced their attitudes toward Advance Directives (AD) and to compare a cohort of 2013 doctors to a 1989 (one year before the Patient Self Determination Act in 1990) cohort to determine any changes in attitudes towards AD in the past 23 years. DESIGN: Doctors in two academic medical centers participated in an AD simulation and attitudes survey in 2013 and their responses were compared to a cohort of doctors in 1989. OUTCOMES: Resuscitation and organ donation preferences (2013 cohort) and attitudes toward AD (1989 and 2013 cohorts). RESULTS: In 2013, 1081 (94.2%) doctors of the 1147 approached participated. Compared to 1989, 2013 cohort did not feel that widespread acceptance of AD would result in less aggressive treatment even of patients who do not have an AD (p<0.001, AUC = 0.77); had greater confidence in their treatment decisions if guided by an AD (p<.001, AUC = 0.58) and were less worried about legal consequences of limiting treatment when following an AD (p<.001, AUC  = 0.57). The gender (p = 0.00172), ethnicity (χ(2) 14.68, DF = 3,p = .0021) and sub-specialty (χ(2) 28.92, p = .004, DF = 12) influenced their attitudes towards AD. 88.3% doctors chose do-not-resuscitate status and wanted to become organ donors. Those less supportive of AD were more likely to opt for “full code” even if terminally ill and were less supportive of organ donation. CONCLUSIONS: Doctors' attitudes towards AD has not changed significantly in the past 23 years. Doctors' gender, ethnicity and sub-specialty influence their attitudes towards AD. Our study raises questions about why doctors continue to provide high-intensity care for terminally ill patients but personally forego such care for themselves at the end of life.